VOCURE: Development and Evaluation of a Card Game-Based Instructional Tool for Teaching Ohm’s Law - Jesica Paterno; Mary Lyn Bombarda; Jose Lu-ib; Aldrin Boocan; Christzon Pasigon (CV. Samuel Manurung and Co, 2026)
Physics is often perceived as a challenging subject due to students’ difficulty in understanding formulas, equations, and real-life applications, particularly in topics such as Ohm’s Law. To address these learning challenges, this study developed and evaluated VOCURE, a card game-based instructional tool designed to enhance conceptual understanding of voltage, current, and resistance through interactive gameplay. Using a preliminary Research and Development (R&D) approach, the 81-card VOCURE deck was assessed by 60 participants, including 50 pre-service and 10 in-service science teachers, on card design, clarity of rules, conceptual accuracy, and playability through a Likert-scale questionnaire. Results showed high ratings across all domains, indicating the game’s potential as an engaging and effective tool for teaching Ohm’s Law. Future research is recommended to include student-based trials and pre- and post-test assessments to determine the game’s impact on actual learning outcomes